2017
DOI: 10.1007/s12079-017-0415-5
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for LPP in metastatic cancer progression

Abstract: LIM domain containing proteins are important regulators of diverse cellular processes, and play pivotal roles in regulating the actin cytoskeleton. Lipoma Preferred Partner (LPP) is a member of the zyxin family of LIM proteins that has long been characterized as a promoter of mesenchymal/fibroblast cell migration. More recently, LPP has emerged as a critical inducer of tumor cell migration, invasion and metastasis. LPP is thought to contribute to these malignant phenotypes by virtue of its ability to shuttle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 174 publications
(266 reference statements)
0
26
0
Order By: Relevance
“…LPP is a member of the zyxin family of LIM proteins and is known to promote mesenchymal migration (38). LPP contains three LIM domains and a proline-rich aminoterminal region (PRR), which allow it to localize to adhesions and interact with numerous proteins (39). While loss of SHCA negatively impacts breast tumor initiation and growth (24), LPP is dispensable for primary tumor growth (37).…”
Section: Morementioning
confidence: 99%
See 1 more Smart Citation
“…LPP is a member of the zyxin family of LIM proteins and is known to promote mesenchymal migration (38). LPP contains three LIM domains and a proline-rich aminoterminal region (PRR), which allow it to localize to adhesions and interact with numerous proteins (39). While loss of SHCA negatively impacts breast tumor initiation and growth (24), LPP is dispensable for primary tumor growth (37).…”
Section: Morementioning
confidence: 99%
“…LPP is a member of the zyxin family of LIM proteins (50). It is able to localize to adhesions and interact with LIM and SH3 protein (LASP), palladin, protein phosphatase 2A (PP2A), scrib, supervillin and vasodilator-stimulated phosphoprotein (VASP) (39). We have previously identified LPP as a promoter of efficient breast cancer lung metastasis (37).…”
Section: Shca Regulates Lpp Recruitment and Retention In Cellular Adhmentioning
confidence: 99%
“…LPP (LIM domain containing preferred translocation partner in lipoma) is a member of the zyxin family of LIM proteins that is characterized as a promoter of mesenchymal/fibroblast cell migration. LPP has been shown to be a critical inducer of tumor cell migration, invasion and metastasis by virtue of its ability to localize to adhesions and to promote invadopodia formation (Ngan et al, 2018). A genome-wide association study of 253 Chinese individuals with B-cell NHL also identified a new susceptibility locus between BCL6 and LPP that was significantly associated with the increased risk of B-cell NHL (Tan et al, 2013).…”
Section: Literature Mining Consolidation Of Results and Selection Omentioning
confidence: 99%
“…LPP (LIM domain containing preferred translocation partner in lipoma) is a member of the zyxin family of LIM proteins that is characterized as a promoter of mesenchymal/fibroblast cell migration. LPP has been shown to be a critical inducer of tumor cell migration, invasion and metastasis by virtue of its ability to localize to adhesions and to promote invadopodia formation (Ngan et al, 2018 (Loveday et al, 2011;Chen et al, 2018). The final selection of a candidate in this family will be based on further functional studies.…”
Section: Literature Mining Consolidation Of Results and Selection Ofmentioning
confidence: 99%